Recreating faith. Religious manifestations in an urban popular sector of Mérida - Várguez Pasos, Luis A. (2000)
This article is located in the complex plot that surrounds the boom that religious activities have acquired in Mexico. I narrate the Sitio de Jericho and the Marian Cenacle. That is to say, various sets of religious activities that take place in the Cristo Rey parish in Mérida, the participation of the priests of that parish and that of the faithful attending these activities. From my perspective, and for analysis purposes, these activities can be seen , on the one hand, as the empirical strategy that I resort to in order to understand its meaning, the forms of insertion of the faithful in them and the ways in which they impact and, on the other, as the actions that the hierarchy of that parish undertakes to maintain its hegemony, retain its faithful in light of the numerous religious offer and fill that void that the Mexican State has left.